2010
DOI: 10.1007/s10152-010-0205-4
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and diversity across rocky intertidal elevation gradients in Helgoland: testing predictions from an environmental stress model

Abstract: Environmental stress affects species richness and diversity in communities, but the precise form of the relationship is unclear. We tested an environmental stress model (ESM) that predicts a unimodal pattern for total richness and diversity in local communities across the full stress gradient where a regional biota can occur. In 2008, we measured richness and diversity (considering all macrobenthic species) across the entire intertidal range on three rocky shores on Helgoland Island, Germany. Intertidal elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Physical stresses such as wave action are also known to influence community structure at the shore scale [47]. In Helgoland, in situ measurements using dynamometers have revealed that wave exposure is higher at Bunker than at Nord-Ost-Hafen and Kringel, being similar between these last two shores [46]. Thus, wave exposure might explain the horizontal variation at the shore scale to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…Physical stresses such as wave action are also known to influence community structure at the shore scale [47]. In Helgoland, in situ measurements using dynamometers have revealed that wave exposure is higher at Bunker than at Nord-Ost-Hafen and Kringel, being similar between these last two shores [46]. Thus, wave exposure might explain the horizontal variation at the shore scale to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…These species commonly occur sympatrically on North Atlantic rocky shores (Scrosati and Heaven 2007;Scrosati et al 2011), with N. lapillus being one of the main predators of S. balanoides (Largen 1967).…”
Section: Methodsmentioning
confidence: 99%
“…In June 2010, we collected dogwhelks from a wavesheltered section of Helgoland's shoreline (mean (SE) daily maximum water velocity of 2.0 ± 0.2 m·s -1 ; Scrosati et al 2011), kept the organisms in a tank with running seawater at 16°C, and fed them barnacles and mussels for 20 days prior to experimentation. We collected the experimental barnacles by chipping off small pieces of rocks to which barnacles were attached on the same shore, using a hammer and a chisel.…”
Section: Methodsmentioning
confidence: 99%
“…This latter procedure is common (e.g. Scrosati et al 2011) and the same unit among abundances is necessary to assess the community dominance profiles in our treatments. The cover was estimated per species, so the total summed % in a plot often exceeded 100%.…”
Section: Legendmentioning
confidence: 99%